Subsidies, spillovers and exports - Sourafel Girma; Holger Görg; Ignat Stepanok (Economics Letters, 2020)
We ask whether production related subsidies have a role to play in explaining Chinesefirms' export performance. We, firstly, implement an estimation approach that allows for both direct and indirect ("spillover") effects of the subsidy on the probability to export. Secondly, our approach enables us to allow these two effects to differ depending on the share of firms that already receive subsidies in a well-specified cluster. These two issues have, to the best of our knowledge, not been considered in evaluations of subsidies on export performance. Our estimation results provide a sobering assessment of the role of production related subsidies in stimulating export performance.
Keywords: F14; F12; H25; 330; Subsidies; Spillovers